Integration of Bioethics and Humanities in Dentistry: A Narrative of an Educational Experience (Revista Iberoamericana de Bioética, 2025)
Given the importance of training our students in values with a view to caring for the health and well-being of patients, the Faculty of Dentistry of the University of Talca is working with special interest in transversally expanding bioethical training across the curricular grid. Furthermore, the implicit challenges of moral teaching in dentistry make it necessary to implement innovative methodologies that generate experiences that can be projected throughout the professional life. Specifically, this work aims to share the experience of a particular academic activity developed during the third year of the degree, together with the foundations and motivations of the academic body.
Keywords: bioethics; teaching; values; dentistry; transdiscipline